ANALISIS FUNGSI MANAJEMEN PEMBERITAAN DI LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA (LPP RRI) AMBON - Yuni Amelia Ipaenin (ADISAM PUBLISHER, 2023)
This research is a descriptive qualitative research that aims to analyze the application of management functions in news at RRI Ambon. This research was conducted at RRI Ambon. Primary data collection was carriedout through interviews with a number of informants who were considered directly involved in the Application of the News Management Function at the Public Broadcasting Corporation of the Republic of Indonesia Radio (LPP RRI) Ambon. The results of this study, namely the application of the news management functionat Radio Republic Indonesia: (1) Implementation of the planning function in the news at RRI. The planning stage that has been arranged based on predetermined provisions has even been well programmed. (2) The application of the organizing function in the news at RRI is in accordance with what should be needed in a radio broadcasting media, the application of the organizing function has achieved the goals / objectives of the news at RRI. (3) Implementation of the implementation function in the news at RRI by informing all employees (journalists) to make preparations to make preparations so that they can carry out the programs that have been made to be done immediately. (4) Supervisory Function, The application of the supervisory function carried out by the news is every activity that has been carried out by making an Accountability Report in the form of financial reports, work reports and other reports at Radio Republik Indonesia so that all employees can read and know the report transparently